Imperfectly competitive cycles with Keynesian and Walrasian features - Leo Kaas; Paul Madden (Institute for Advanced Studies (IHS), 2000)
We consider a multi-sector overlapping generations model with imperfectly competitive firms in the output markets and wage setting trade unions in the labour markets. A coordination problem between firms creates multiple temporary equilibria which are either Walrasian or of the Keynesian unemployment type. There exist many deterministic and stochastic equilibrium cycles fluctuating between Keynesian recession and Walrasian boom periods with arbitrarily long phases in each regime. The cycles are in accordance with certain empirical regularities. Money is neutral and superneutral, but appropriate countercyclical fiscal policies stabilize the cycles in a textbook Keynesian way.
Keywords: D43; E32; E62; 330; endogenous business cycles; imperfect competition; stabilization policy; Konjunkturtheorie; Unvollkommener Wettbewerb; Finanzpolitik; Theorie